Age-Related Volumetric Changes in Mandibular Condyles. Issue 2 (March 2018) - Safi, Ali-Farid; Kauke, Martin; Grandoch, Andrea; Nickenig, Hans-Joachim; Zöller, Joachim E.; Kreppel, Matthias
Abstract : Abstract: A precise knowledge of the condylar changes with advancing age may improve understanding of pathophysiological alterations of the mandibular condyles. However, the majority of studies focusses on morphological changes, although volumetric analysis based upon cone beam computerized tomography may provide important additional data to characterize mandibular condyles. Therefore, we aimed to provide and compare volumetric data of mandibular condyles of a young and old patient group. This is a retrospective chart review of 195 patients with cone beam computerized tomography between 2007 and 2016. Student t test, analysis of variance, and Pearson correlation test were performed to analyze associations between categorical and continuous variables. P values <0.05 were considered as significant. Volume measurement was performed in a semiautomatic segmentation method with the program "ITK-Snap." Side- and sex-specific significant differences between condylar volumes were found both in the young and old patient cohort. Age and posterior occlusal support did not significantly correlate with the condylar volume. Volumetric measurement of the mandibular condyles may serve as an important additional characteristic, derived from 3-dimensional imaging. Significant differences in volumetric measurement of mandibular condyles exist between sex and side, but not in relation to age and occlusal support.